The relationship of motor vehicles and soil lead levels in Pingtung, Taiwan - Liao, Yen-Hsiung (SPC Journal of Environmental Sciences, 2021)
Purpose: Most of lead consumption is for the motor vehicles. The soil is polluted by leaded aviation fuel. Approach: Using enrolled motor vehicles during 1995 â€“ 2018. We approached the effect of lead emission on soil quality of Pingtung County that is known its agriculture in Taiwan. Results: The enrolled motor vehicles was peak in 2011, The mean lead levels in soil was peak in 2013. The enrolled motor vehicles was correlated to the mean lead levels in soil significantly ( r = 0.71, p < 0.05). Soil quality was not improved after the banned or reduced lead in gasoline product. Conclusions: Decreasing motor vehicles could cause a lower contaminated lead level in soil. The soil should be protected by diminishing automobile emission. Â Â